Election Insecurity in Social Media Campaigns: An Analysis of the 2024 Indonesian Presidential Election - Muh Khamdan; Nadiah Abidin; Wiharyani (Fenomena, 2025)
This article examines changes in campaign patterns and the mobilization of political support through online media. This shift in campaign strategy provides competing political groups with opportunities to innovate in their use of digital media tools. Political contestation necessitates access to alternative information sources beyond mainstream media. However, social media, which allows individuals to autonomously convey political views and calls to action, carries the risk of political vulnerability through hate speech and misinformation. This paper employs a qualitative method, analyzing data through content analysis based on Norman Fairclough’s Critical Discourse Analysis model, which emphasizes textual, practical, and socio-cultural dimensions. The primary sources for this article are documents concerning evolving patterns of presidential election contestation in online media and activities interpreting political contestation. Socio-cultural analysis reveals that the voting public in the presidential election tends to acquire knowledge of diversity through social media rather than direct mobilization, potentially contributing to increased tensions in Indonesia’s political contestation. Artikel ini menggambarkan perubahan pola kampanye dan mobilisasi dukungan politik di melalui media online. Perubahan strategi kampanye tersebut memberikan peluang bagi kelompok-kelompok politik yang berkontestasi untuk lebih kreatif memanfaatkan instrumen media. Kontestasi politik sangat membutuhkan ketersediaan alternatif sumber-sumber informasi di luar media mainstream. Persoalannya, pemanfaatan media sosial yang sangat otonom bagi individu untuk menyampaikan pandangan dan ajakan politik, memiliki potensi kerawanan politik akibat adanya ujaran kebencian dan pelintiran kebenaran. Tulisan ini menggunakan metode kualitatif yang menjelaskan data dengan metode analisis isi menggunakan teori critical discourse analysis model Norman Fairclough, yang menitikberatkan pada analisis teks, praktik, dan sosial kultural. Sumber utama artikel ini adalah dokumen-dokumen terkait pergeseran pola kontestasi pemilihan presiden di media online dan aktivitas interpretasi kontestasi politik. Hasil analisis sosiokultural menjelaskan bahwa situasi masyarakat pemilih dalam pemilihan presiden memiliki kecenderungan mengambil pengetahuan keberagaman melalui media sosial daripada mobilisasi langsung, sehingga berpotensi memunculkan konflik dalam kontestasi politik di Indonesia.